Bioactive tanshinone I inhibits the growth of lung cancer in part via downregulation of Aurora A function - Li, Yanli (2012)
Lung cancer is the leading cause of cancer death in the world, and the searching for novel efficacious and safe agents for lung cancer prevention remains the top priority of lung cancer research. In the present study, we evaluated the effect of bioactive tanshinones from a Chinese herb Salvia Miltiorrhiza, Cryptotanshinone (CT), Tanshinone I (T1) and Tanshinone IIA (T2A), on the proliferation inhibition of lung cancer cell lines. Tanshinones inhibited the lung cancer cell proliferation in vitro, with T1 the most potent, via cell cycle arrest and apoptosis induction. Gene function assay showed that Aurora A knockdown by siRNA dramatically eliminated the T1 activity in vitro, suggesting that Aurora A is an important functional target for T1. We further evaluated the effectiveness of T1 on the growth of H1299 non-small lung cancer cell in a mouse model. Tanshinone I inhibited the growth of H1299 lung tumor in a dose-dependent manner. Tanshinone I at 200mg/kg body weight significantly reduced final tumor weight by 34% (P<0.05) associated with inhibiting proliferation and inducing apoptosis of lung cancer cells by 54% (P<0.001) and 193% (P<0.001) respectively, inhibiting lung tumor angiogenesis by 72% (P<0.001), and reducing Aurora A expression by 67% (P<0.001). On the other hand, T1 did not significantly alter food intake or body weight. Our results provided experimental evidence to suggest that T1 may be an efficacious and safe agent for the prevention of lung cancer progression and Aurora A may be an important molecular target for T1 action against lung cancer.